Method for preparing wall material by using carbon dioxide curing process
By controlling the ratio of aggregates and fillers and preparing enhancers for low-temperature thermal activation processes, the efficient capture and utilization of CO2 at room temperature and pressure is achieved, and the problems of low CO2 utilization rate and complex process in the existing technology are solved, and the problems of high-quality CO2 utilization rate and complex process are improved. The strength and wear resistance of wall materials are suitable for the production of pavement tiles and permeable tiles.
Patent Information
- Application Number
- CN202411304603.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The existing CO2 curing concrete technology has problems in its application, such as low CO2 utilization, complex process and poor economic performance. Especially when large-scale production of reinforced concrete components, it is difficult to achieve efficient CO2 penetration depth and density, which limits its wide range. application.
A method of preparing wall materials using carbon dioxide maintenance technology is adopted. By controlling the particle size and proportion of aggregates and fillers, and combining low-temperature thermal activation technology to prepare enhancers and water glass inducers, so as to achieve low concentration of CO2 at room temperature and pressure. Efficient capture, utilization and storage, simplify process routes, and improve the strength and wear resistance of wall materials.
It realizes efficient capture and utilization of low concentration CO2 at room temperature and pressure, shortens the process route, improves the preparation efficiency and performance of wall materials, is suitable for the production of pavement bricks and permeable bricks, and solves the CO2 in the existing technology. Low utilization and complex process problems.
Smart Images

Figure CN119191875A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing wall materials by utilizing a carbon dioxide curing process. Background Art
[0002] Global warming caused by greenhouse gases will lead to a series of serious environmental problems. Carbon dioxide (CO2) is the most important greenhouse gas, and its control and emission reduction are of great significance to mitigating climate change. Therefore, it is very necessary to reduce CO2 emissions in the utilization of fossil resources, and carbon capture, utilization and storage (CCUS) technology is currently the only technical option to achieve large-scale low-carbon utilization of fossil energy. CCUS technology can be divided into four important links according to the technical process: carbon capture, carbon transportation, carbon utilization and carbon storage. Among them, CO2-cured concrete technology has been regarded as one of the most promising technologies for large-scale storage of CO2 in recent years.
[0003] At present, scholars generally believe that CO2-cured concrete means that when the hydration process of fresh concrete has not yet been completed, the oxides (mainly calcium silicate and calcium aluminate) in the cement particles that have not yet been hydrated and part of the hydration product Ca(OH)2 react chemically with CO2 to generate calcium carbonate CaCO3 and silica gel, which hardens the cement and concrete and rapidly develops strength. Since the main product of this reaction is insoluble calcium salt, the CSH gel pores and some capillaries of the concrete will be blocked by the carbonization products, which will increase the density and strength of the concrete, and to a certain extent, will also hinder the diffusion speed of CO2 into the concrete, further improving the compression and flexural strength of concrete products and the frost resistance, impact resistance and wear resistance. During the research, it was found that when fresh concrete is treated with CO2 surface treatment, CO2 will react with tricalcium silicate, dicalcium silicate and other substances in cement particles, and will also react with calcium hydroxide, a cement hydration product. The volume increases before and after the reaction. Therefore, the reaction can increase the solid volume of the product, which is beneficial to improving the density of cement-based materials. The generated calcium carbonate has better stability, so that the products after the reaction have better surface wear resistance and water resistance.
[0004] The main factors that affect the quality of CO2-cured concrete products are: CO2 concentration, ambient temperature, ambient relative humidity, water-cement ratio, etc.; the most important factor is the CO2 penetration depth. During the curing process, CO2 travels with water in the form of carbonic acid, and reacts with concrete during the penetration process, and the products will further hinder the penetration path. There are also many ways to increase the penetration depth, such as increasing the CO2 concentration, increasing the environmental pressure during the reaction process, etc. However, when these methods are used for reinforced concrete components for construction, their large-scale application is greatly limited due to the large and irregular size of the components. In addition, the cost of CO2 to increase the penetration depth during the curing process is relatively huge, and the economic efficiency is not good. Therefore, the development of a concrete product that only requires surface strengthening, or whose structure itself is conducive to CO2 penetration, will become the key to whether CO2-cured concrete technology can be applied at a high value.
[0005] At the same time, although the technology of using CO2 to prepare wall materials has been studied for many years, it is still basically in the theoretical research stage. In the current research results, the source of CO2 is the bottleneck restricting the application of this technology. The CO2 used in the laboratory research stage is mostly industrial high-purity CO2, which is expensive and requires complex processes to support it. From the perspective of large-scale storage of CO2, the utilization rate is not high, which is actually a waste of existing resources.
[0006] In summary, finding a type of building materials product that can be maintained with a lower concentration of CO2 and can be produced using existing equipment, while the producer being self-sufficient in the CO2 required, and integrating the four links of carbon capture, carbon transportation, carbon utilization and carbon storage of CCUS technology into one production link, and the products produced by this method have significantly improved performance, has become an urgent problem to be solved in this field. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing wall materials using a carbon dioxide curing process in view of the shortcomings of the above-mentioned prior art. The method prepares wall materials through carbon dioxide curing, realizes the efficient capture, utilization and storage of low-concentration CO2 at normal temperature and pressure, greatly shortens the process route, ensures the quality and performance of the wall materials, improves the preparation efficiency of the wall materials, and solves the problem that the existing technology of preparing wall materials using CO2 is complex and the CO2 utilization rate is low.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing wall materials using a carbon dioxide curing process, characterized in that the method uses aggregate, filler, cementitious material, reinforcing agent, inducer, and water as raw materials, and prepares the wall material through primary stirring, secondary stirring, standing, pressing and molding, and carbon dioxide curing.
[0009] The above-mentioned method for preparing wall materials using a carbon dioxide curing process is characterized in that the aggregate is derived from natural aggregates and recycled aggregates from construction waste, and the filler is derived from natural sand, artificial sand, recycled sand from construction waste, and industrial tailings sand, wherein the particle size of the aggregate is 3 mm to 5 mm, and the particle size of the filler is less than 1.5 mm. The aggregate and filler used in the present invention can be derived from recycled materials and can absorb industrial tailings, thereby achieving full utilization of resources; at the same time, by controlling the particle size of the aggregate and filler within the above-mentioned range, the filler and the cementitious material are more likely to gather in the area between the contact points of the aggregates, increasing the area of the bonding area, thereby forming a "waist" bonding, avoiding point bonding, and being beneficial to improving the strength of the wall material, and also ensuring the void volume of the entire wall material product, significantly improving the quality of the wall material, especially the permeable bricks.
[0010] The above-mentioned method for preparing wall materials using a carbon dioxide curing process is characterized in that, if the wall material is a pavement brick, the mass proportion of the aggregate in the raw material aggregate and the filler is less than 30%, and the mass proportion of the filler is greater than 70%; or if the wall material is a permeable brick, the mass proportion of the aggregate in the raw material aggregate and the filler is greater than 40%, and the mass proportion of the filler is less than 60%.
[0011] The wear resistance of pavement bricks is a key performance indicator. The present invention adopts a carbon dioxide curing process to strengthen the surface of pavement bricks and significantly improve the quality of pavement brick products. Permeable bricks require sufficient non-closed gaps, but too many gaps easily lead to insufficient density of permeable brick products, and their strength and durability cannot be guaranteed. The present invention adopts a carbon dioxide curing process, controls the proportion of aggregates and fillers in different types of wall materials, adjusts the strength and void amount of wall materials, and ensures that carbon dioxide enters the interior through the gaps of wall materials for strengthening, thereby preparing pavement bricks and permeable bricks respectively, ensuring the quality of wall materials.
[0012] The above-mentioned method for preparing wall materials using a carbon dioxide curing process is characterized in that the cementitious material is silicate cement, the reinforcing agent raw material is two or more of dolomite, mica, lime and diopside, and the reinforcing agent contains the following chemical components by mass fraction: CaO>30%, MgO+Na2O+K2O>10%, SO3<0.50%, and the reinforcing agent is prepared by a low-temperature thermal activation process: the reinforcing agent raw material is placed in an electric furnace and kept warm at 80°C for 20 minutes, 110°C for 1 hour, 400°C for 20 minutes, and 600°C for 1 hour, and after cooling to room temperature with the furnace, it is immediately transferred to a crusher for mechanical activation, and then crushed to 400 mesh, and sealed and stored for standby use; the inducer is water glass or sodium hydroxide.
[0013] The present invention selects the above-mentioned reinforcing agent and controls the reinforcing agent to be prepared by a low-temperature thermal activation process, thereby ensuring the chemical composition of the reinforcing agent. The highly active CaO in the chemical composition of the reinforcing agent is more likely to form dense CaCO3 in a low-concentration carbon dioxide curing environment, thereby improving the sensitivity of the curing process. An appropriate amount of active alkaline metals including MgO, Na2O, and K2O promote the polymerization of the cementitious material, thereby enhancing the bonding effect of the cementitious material and helping to improve the strength of the wall material. The inducer has an auxiliary effect on the active alkaline metal. The sodium silicate in the preferred inducer water glass participates in the CO2 curing reaction to generate CSH gel, thereby increasing the CSH gel content and helping to fill micropores, thereby improving the wear resistance and waterproofness of the wall material.
[0014] The method for preparing wall materials using a carbon dioxide curing process is characterized in that the total mass of the aggregate and filler accounts for 80% to 90% of the dry material, the mass of the cementitious material accounts for 10% to 20%, and the mass of the reinforcing agent added is 5% to 10% of the dry material mass, the mass of the inducing agent added is 3% to 5% of the dry material mass, and the mass of water added is 10% to 20% of the dry material mass. The preparation process includes the following steps:
[0015] Step 1, mixing and standing the raw materials: weigh the aggregate, filler, cementitious material, and reinforcing agent, pour them into a mixer for dry material mixing to obtain a mixed dry material, and at the same time weigh the inducer and water, pour them into a high-speed mixer for wet material mixing to obtain a mixed slurry, and then introduce the mixed slurry into the mixed dry material for secondary mixing, and then stand to obtain a preformed material;
[0016] Step 2: Compression molding: the preformed material obtained in step 1 is placed into a mold and then subjected to static compression molding to obtain a pressed blank;
[0017] Step 3, carbon dioxide curing: the green compact obtained in step 2 is placed in a steam curing kettle in a carbon dioxide curing device and sealed, carbon dioxide is introduced into the steam curing kettle through a carbon dioxide compensator, and the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank is sent into the steam generator, and the green compact is subjected to carbon dioxide curing to obtain a wall material.
[0018] The above-mentioned method for preparing wall materials using a carbon dioxide curing process is characterized in that the rotation speed of the dry material stirring in step one is 20 r / min, and the stirring time is 3 min; the rotation speed of the wet material stirring is 500 r / min, and the stirring time is 2 min; the rotation speed of the secondary stirring is 45 r / min, and the stirring time is 2 min; and the standing time is 1 h to 4 h.
[0019] The above-mentioned method for preparing wall materials using a carbon dioxide curing process is characterized in that the pressure of the static pressing molding in step 2 is not less than 25 MPa, and the loading speed is not greater than 0.8 MPa / s.
[0020] The above-mentioned method for preparing wall materials using a carbon dioxide curing process is characterized in that the carbon dioxide battery liquid in step three is a mixed liquid of water and an absorbent, wherein the absorbent is prepared by mixing lithium slag, sodium hydroxide, lithium carbonate, and potassium carbonate in a mass ratio of 1:1:1.5:1, calcining at 600°C for 30 minutes, and then grinding to 300 mesh, and the solid-liquid ratio of the carbon dioxide battery liquid is 1:100.
[0021] In the prior art, potassium carbonate solution, alcohol amine aqueous solution, organic amine solution or ammonia water are usually used as absorbents for CO2 treatment. This method has a high CO2 absorption rate, but has high requirements on the absorption temperature (60℃~80℃) and requires a high CO2 partial pressure (concentration). It is mainly used in the smoke exhaust system of thermal power plants or chemical plants, and requires special CO2 analysis equipment, which is difficult to promote and apply. During the research process of the present invention, it was found that the absorption liquid prepared by mixing industrial lithium slag with water after low-temperature pre-calcination and grinding in an alkaline environment has a significant absorption efficiency for low-concentration carbon dioxide. Therefore, a carbon dioxide battery liquid mixed with water and an absorbent is designed. By adding sodium hydroxide and potassium carbonate to the absorbent to provide an alkaline environment, and adding lithium carbonate to adjust the lithium content in the absorbent, a carbon dioxide battery liquid that is sensitive to low-concentration CO2 and has a high CO2 absorption rate is obtained. The carbon dioxide battery liquid is more suitable for capturing CO2 in an atmospheric environment at normal temperature and pressure, thereby improving the CO2 capture efficiency and facilitating CO2 transportation. At the same time, the carbon dioxide battery liquid after absorbing CO2 is directly used in a carbon dioxide curing process, and CO2 is analyzed and released under high-temperature and high-pressure curing conditions. After CO2 enters the compact, it participates in the curing reaction to generate solid phase substances such as calcium carbonate, thereby realizing the utilization and storage of CO2 and shortening the process route.
[0022] The above-mentioned method for preparing wall materials using a carbon dioxide curing process is characterized in that, in step three, when the wall material is a pavement brick, the specific process of carbon dioxide curing is: turn on the vacuum pump to evacuate the steam curing kettle body to a pressure of -0.1MPa, stop evacuating and close the pipeline to stabilize the pressure in the steam curing kettle body, then turn on the carbon dioxide compensator to introduce carbon dioxide into the steam curing kettle body until the pressure reaches 0MPa, then stop and stop for 5 minutes, and at the same time, send the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank into the steam generator through the feed pipe, start the heating rod for heating, and perform carbon dioxide curing on the pressed blank, the curing temperature is 180°C, the pressure in the kettle is 0.8MPa, the pressure and heat preservation time is 5h, and then the used carbon dioxide battery liquid is sent to the carbon dioxide absorption tank through the liquid outlet pipe, and the steam curing kettle body is depressurized.
[0023] The method for preparing wall materials using a carbon dioxide curing process is characterized in that, in step three, when the wall material is a permeable brick, the specific process of carbon dioxide curing is: turn on the vacuum pump to evacuate the steam curing kettle body to a pressure of -0.06MPa, stop evacuating and close the pipeline to stabilize the pressure in the steam curing kettle body, then turn on the carbon dioxide compensator to introduce carbon dioxide into the steam curing kettle body until the pressure reaches 0MPa, then stop and stop for 5 minutes, and at the same time, send the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank into the steam generator through the feed pipe, start the heating rod for heating, and perform carbon dioxide curing on the pressed blank, the curing temperature is 180°C, the pressure in the kettle is 0.8MPa, the pressure and heat preservation time is 3h, and then the used carbon dioxide battery liquid is sent to the carbon dioxide absorption tank through the liquid outlet pipe, and the steam curing kettle body is depressurized.
[0024] The saturated carbon dioxide battery liquid of the present invention has strict requirements on the CO2 analysis environment. It is usually necessary to control the pressure in the tank to 0.6MPa-0.8MPa, and more preferably 0.8MPa, to avoid the risk of failure of the carbon dioxide battery liquid due to excessive pressure. At the same time, this pressure range just meets the requirements for autoclaving and curing concrete products (0.75MPa), thereby completing the curing of wall material products while analyzing the carbon dioxide battery liquid, greatly improving the preparation efficiency.
[0025] At the same time, the present invention aims at two types of wall materials, namely pavement bricks and permeable bricks. On the one hand, the proportion of components in the raw materials, especially aggregates and fillers, is controlled, and on the other hand, a special maintenance system is designed in combination with the maintenance characteristics of low CO2 maintenance concentration, thereby achieving the capture of CO2 at normal temperature and pressure, the analysis, utilization and storage of carbon dioxide battery fluid, and ensuring the performance of pavement bricks and permeable bricks.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1. The present invention performs CO2 curing on the pressed green sheets to prepare wall materials. By controlling the raw materials of the pressed green sheets and thus controlling their structure, it is beneficial for CO2 to enter and exert a strengthening effect, thereby achieving efficient capture of low-concentration CO2 at normal temperature and pressure, ensuring the quality and performance of the wall materials, and improving the preparation efficiency of the wall materials.
[0028] 2. The present invention adopts carbon dioxide battery fluid to carry out carbon dioxide curing process. By controlling the composition of carbon dioxide battery fluid, the collection and utilization of low-concentration carbon dioxide is realized, and the utilization and storage of CO2 are realized at the same time, which greatly shortens the process route and expands the scope of application of the method of the present invention.
[0029] 3. The present invention adds a reinforcing agent component to the raw materials for preparing the wall material, thereby increasing the sensitivity of the pressed green sheets made from the raw materials to CO2 during the CO2 curing process, increasing the utilization of CO2, and being beneficial to improving the strength performance of the wall material.
[0030] 4. The present invention controls the properties and proportions of aggregates and fillers in the raw materials for preparing wall materials, combines targeted design of CO2 curing system, and effectively adjusts the void structure and strength performance of wall materials, thereby obtaining two wall materials with different performances, namely pavement bricks and permeable bricks, thereby ensuring the quality of wall materials and being suitable for different environments.
[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the structure of the carbon dioxide curing device used in the present invention.
[0033] Description of Reference Numerals
[0034] 1—Vacuum pump; 2—Carbon dioxide compensator; 3—Steam curing kettle body;
[0035] 4—Carbon dioxide absorption tank; 5—Steam generator; 6—Heating rod. DETAILED DESCRIPTION
[0036] like Figure 1 As shown, the carbon dioxide curing device used in Examples 1 to 4 of the present invention includes a steam curing kettle body 3 and a steam generator 5 connected to the steam curing kettle body 3, wherein a heating rod 6 is arranged in the steam generator 5, and the steam curing kettle body 3 is respectively connected to a vacuum pump 1 and a carbon dioxide compensator 2, the steam generator 5 is connected to a carbon dioxide absorption tank 4, and a feed pipe and a liquid outlet pipe are arranged between the steam generator 5 and the carbon dioxide absorption tank 4.
[0037] Example 1
[0038] This embodiment includes the following steps:
[0039] Step 1, mixing and standing the raw materials: weigh the recycled aggregate of construction waste with a particle size of 3mm to 5mm, the natural sand filler with a particle size of less than 1.5mm, the silicate cement binder, and the reinforcing agent, pour them into a mixer and stir the dry material at a speed of 20r / min for 3min to obtain a mixed dry material. At the same time, weigh the inducer water glass and water, pour them into a high-speed mixer and stir the wet material at a speed of 500r / min for 2min to obtain a mixed slurry, and then introduce the mixed slurry into the mixed dry material and stir it for a second time at a speed of 45r / min for 2min, and then stand it for 4h to obtain a preformed material;
[0040] The reinforcing agent is prepared by a low-temperature thermal activation process: the reinforcing agent raw materials dolomite, mica, and diopside are placed in an electric furnace at a mass ratio of 4:4:2 and kept at 80°C for 20 minutes, 110°C for 1 hour, 400°C for 20 minutes, and 600°C for 1 hour. After the furnace is cooled to room temperature, it is immediately transferred to a crusher for mechanical activation, and then crushed into 400 meshes, sealed and stored for standby use. The mass fractions of the chemical components contained in the reinforcing agent are shown in Table 1 below:
[0041] Table 1
[0042]
[0043] The total mass proportion of the recycled aggregate from construction waste and the natural sand filler is 90% based on dry matter, and the mass ratio of the recycled aggregate from construction waste and the natural sand filler is 30:70, the mass proportion of the silicate cement binder is 10%, and the mass of the reinforcing agent added is 10% of the mass of the dry material, the mass of the inducing agent water glass added is 5% of the mass of the dry material, and the mass of the water added is 20% of the mass of the dry material;
[0044] Step 2, compression molding: the preformed material obtained in step 1 is placed into a mold and then subjected to static compression molding to obtain a compact; the static compression molding pressure is 25 MPa, and the loading speed is not greater than 0.8 MPa / s;
[0045] Step 3, carbon dioxide curing: the green compact obtained in step 2 is placed in a steam curing kettle tank body 3 in a carbon dioxide curing device and sealed, carbon dioxide is introduced into the steam curing kettle tank body 3 through a carbon dioxide compensator 2, and the saturated carbon dioxide battery liquid in a carbon dioxide absorption tank 4 is simultaneously sent into a steam generator 5, and the green compact is subjected to carbon dioxide curing to obtain a wall material pavement brick;
[0046] The carbon dioxide battery liquid is a mixed liquid of water and an absorbent, wherein the absorbent is prepared by mixing lithium slag, sodium hydroxide, lithium carbonate, and potassium carbonate in a mass ratio of 1:1:1.5:1, calcining at 600° C. for 30 minutes, and then grinding to 300 meshes, and the solid-liquid ratio of the carbon dioxide battery liquid is 1:100;
[0047] The specific process of the carbon dioxide curing is: open the vacuum pump 1 to evacuate the autoclave tank body 3 to a pressure of -0.1MPa, stop evacuating and close the pipeline to stabilize the pressure in the autoclave tank body 3, then open the carbon dioxide compensator 2 to introduce carbon dioxide into the autoclave tank body 3 until the pressure reaches 0MPa, then stop and stop for 5 minutes, and at the same time, send the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank 4 into the steam generator 5 through the feed pipe, start the heating rod 6 for heating, and perform carbon dioxide curing on the compact, the curing temperature is 180°C, the curing temperature is 180°C, the pressure in the autoclave is 0.8MPa, the pressure and temperature holding time is 5h, and then send the used carbon dioxide battery liquid into the carbon dioxide absorption tank 4 through the liquid outlet pipe, and release the pressure of the autoclave tank body 3.
[0048] After testing, it was found that the strength, wear resistance and other product indicators of the pavement bricks prepared in this embodiment all met the requirements of GB 28635-2012 "Concrete Pavement Bricks".
[0049] The aggregate in this embodiment can also be derived from natural aggregate, the filler can also be derived from artificial sand, construction waste regenerated sand, industrial tailings sand, the inducer can also be derived from sodium hydroxide, and the reinforcing agent raw material can also be two or more of dolomite, mica, lime and diopside other than the combination of dolomite, mica and diopside.
[0050] Example 2
[0051] This embodiment includes the following steps:
[0052] Step 1, mixing and standing the raw materials: weigh the recycled aggregate of construction waste with a particle size of 3mm to 5mm, the natural sand filler with a particle size of less than 1.5mm, the silicate cement binder, and the reinforcing agent, pour them into a mixer and stir the dry material at a speed of 20r / min for 3min to obtain a mixed dry material. At the same time, weigh the inducer water glass and water, pour them into a high-speed mixer and stir the wet material at a speed of 500r / min for 2min to obtain a mixed slurry, and then introduce the mixed slurry into the mixed dry material and stir it for a second time at a speed of 45r / min for 2min, and then stand it for 1h to obtain a preformed material;
[0053] The reinforcing agent is prepared by a low-temperature thermal activation process: the reinforcing agent raw materials dolomite, mica, and diopside are placed in an electric furnace at a mass ratio of 4:4:2 and kept at 80°C for 20 minutes, 110°C for 1 hour, 400°C for 20 minutes, and 600°C for 1 hour. After the furnace is cooled to room temperature, it is immediately transferred to a crusher for mechanical activation, and then crushed into 400 meshes, sealed and stored for standby use. The mass fractions of the chemical components contained in the reinforcing agent are shown in Table 2 below:
[0054] Table 2
[0055]
[0056] The total mass proportion of the construction waste recycled aggregate and natural sand filler is 80% based on dry material, and the mass ratio of the construction waste recycled aggregate and natural sand filler is 40:60, the mass proportion of silicate cement binder is 20%, and the added mass of the reinforcing agent is 5% of the mass of the dry material, the added mass of the inducer water glass is 3% of the mass of the dry material, and the added mass of water is 10% of the mass of the dry material;
[0057] Step 2, compression molding: the preformed material obtained in step 1 is placed into a mold and then subjected to static compression molding to obtain a compact; the static compression molding pressure is 20 MPa, and the loading speed is not greater than 0.8 MPa / s;
[0058] Step 3, carbon dioxide curing: the green compact obtained in step 2 is placed in a steam curing kettle tank 3 in a carbon dioxide curing device and sealed, carbon dioxide is introduced into the steam curing kettle tank 3 through a carbon dioxide compensator 2, and the saturated carbon dioxide battery liquid in a carbon dioxide absorption tank 4 is simultaneously sent into a steam generator 5, and the green compact is subjected to carbon dioxide curing to obtain a permeable brick for a wall material;
[0059] The carbon dioxide battery liquid is a mixed liquid of water and an absorbent, wherein the absorbent is prepared by mixing lithium slag, sodium hydroxide, lithium carbonate, and potassium carbonate in a mass ratio of 1:1:1.5:1, calcining at 600° C. for 30 minutes, and then grinding to 300 meshes, and the solid-liquid ratio of the carbon dioxide battery liquid is 1:100;
[0060] The specific process of the carbon dioxide curing is as follows: the vacuum pump 1 is turned on to evacuate the curing kettle body 3 to a pressure of -0.06MPa, the vacuuming is stopped and the pipeline is closed to stabilize the pressure in the curing kettle body 3, and then the carbon dioxide compensator 2 is turned on to introduce carbon dioxide into the curing kettle body 3 until the pressure reaches 0MPa, and then the pressure is stopped for 5 minutes, and at the same time, the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank 4 is sent to the steam generator 5 through the feeding pipe, and the heating rod 6 is started for heating, and the pressed green body is subjected to carbon dioxide curing, the curing temperature is 180°C, the pressure in the kettle is 0.8MPa, and the pressure and temperature holding time is 3h, and then the used carbon dioxide battery liquid is sent to the carbon dioxide absorption tank 4 through the liquid outlet pipe, and the curing kettle body 3 is depressurized.
[0061] After testing, the product indicators such as strength, wear resistance, and permeability coefficient of the permeable bricks prepared in this embodiment all meet the requirements of GB / T25993-2023 "Permeable Pavement Bricks and Permeable Road Panels".
[0062] Example 3
[0063] This embodiment includes the following steps:
[0064] Step 1, mixing and standing the raw materials: weigh the recycled aggregate of construction waste with a particle size of 3mm to 5mm, the natural sand filler with a particle size of less than 1.5mm, the silicate cement binder, and the reinforcing agent, pour them into a mixer and stir the dry material at a speed of 20r / min for 3min to obtain a mixed dry material. At the same time, weigh the inducer water glass and water, pour them into a high-speed mixer and stir the wet material at a speed of 500r / min for 2min to obtain a mixed slurry, and then introduce the mixed slurry into the mixed dry material and stir it for a second time at a speed of 45r / min for 2min, and then stand it for 4h to obtain a preformed material;
[0065] The reinforcing agent is prepared by a low-temperature thermal activation process: the reinforcing agent raw materials of dolomite, mica, lime and diopside are placed in an electric furnace at a mass ratio of 3:3:2:2 and kept at 80°C for 20 minutes, 110°C for 1 hour, 400°C for 20 minutes and 600°C for 1 hour, and immediately transferred to a crusher for mechanical activation after the furnace is cooled to room temperature, and then crushed to 400 meshes, sealed and stored for standby use, and the mass fractions of the chemical components contained in the reinforcing agent are shown in Table 3 below:
[0066] Table 3
[0067]
[0068]
[0069] The total mass proportion of the recycled aggregate from construction waste and the natural sand filler is 80% based on dry matter, and the mass ratio of the recycled aggregate from construction waste and the natural sand filler is 20:80, the mass proportion of the silicate cement binder is 20%, and the added mass of the reinforcing agent is 5% of the mass of the dry material, the added mass of the inducing agent water glass is 5% of the mass of the dry material, and the added mass of water is 20% of the mass of the dry material;
[0070] Step 2, compression molding: the preformed material obtained in step 1 is placed into a mold and then subjected to static compression molding to obtain a compact; the static compression molding pressure is 25 MPa, and the loading speed is not greater than 0.8 MPa / s;
[0071] Step 3, carbon dioxide curing: the green compact obtained in step 2 is placed in a steam curing kettle tank body 3 in a carbon dioxide curing device and sealed, carbon dioxide is introduced into the steam curing kettle tank body 3 through a carbon dioxide compensator 2, and the saturated carbon dioxide battery liquid in a carbon dioxide absorption tank 4 is simultaneously sent into a steam generator 5, and the green compact is subjected to carbon dioxide curing to obtain a wall material pavement brick;
[0072] The carbon dioxide battery liquid is a mixed liquid of water and an absorbent, wherein the absorbent is prepared by mixing lithium slag, sodium hydroxide, lithium carbonate, and potassium carbonate in a mass ratio of 1:1:1.5:1, calcining at 600° C. for 30 minutes, and then grinding to 300 meshes, and the solid-liquid ratio of the carbon dioxide battery liquid is 1:100;
[0073] The specific process of the carbon dioxide curing is: open the vacuum pump 1 to evacuate the autoclave tank body 3 to a pressure of -0.1MPa, stop evacuating and close the pipeline to stabilize the pressure in the autoclave tank body 3, then open the carbon dioxide compensator 2 to introduce carbon dioxide into the autoclave tank body 3 until the pressure reaches 0MPa, then stop and stop for 5 minutes, and at the same time, send the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank 4 into the steam generator 5 through the feed pipe, start the heating rod 6 for heating, and perform carbon dioxide curing on the compact, the curing temperature is 180°C, the curing temperature is 180°C, the pressure in the autoclave is 0.8MPa, the pressure and temperature holding time is 5h, and then send the used carbon dioxide battery liquid into the carbon dioxide absorption tank 4 through the liquid outlet pipe, and release the pressure of the autoclave tank body 3.
[0074] After testing, it was found that the strength, wear resistance and other product indicators of the pavement bricks prepared in this embodiment all met the requirements of GB 28635-2012 "Concrete Pavement Bricks".
[0075] The aggregate in this embodiment can also be derived from natural aggregate, the filler can also be derived from artificial sand, construction waste regenerated sand, industrial tailings sand, the inducer can also be derived from sodium hydroxide, and the reinforcing agent raw material can also be two or more of dolomite, mica, lime and diopside other than the combination of dolomite, mica and diopside.
[0076] Example 4
[0077] This embodiment includes the following steps:
[0078] Step 1, mixing and standing the raw materials: weigh the recycled aggregate of construction waste with a particle size of 3mm to 5mm, the natural sand filler with a particle size of less than 1.5mm, the silicate cement binder, and the reinforcing agent, pour them into a mixer and stir the dry material at a speed of 20r / min for 3min to obtain a mixed dry material. At the same time, weigh the inducer water glass and water, pour them into a high-speed mixer and stir the wet material at a speed of 500r / min for 2min to obtain a mixed slurry, and then introduce the mixed slurry into the mixed dry material and stir it for a second time at a speed of 45r / min for 2min, and then stand it for 1h to obtain a preformed material;
[0079] The reinforcing agent is prepared by a low-temperature thermal activation process: the reinforcing agent raw materials of dolomite, mica, lime and diopside are placed in an electric furnace at a mass ratio of 3:3:2:2 and kept at 80°C for 20 minutes, 110°C for 1 hour, 400°C for 20 minutes and 600°C for 1 hour, and immediately transferred to a crusher for mechanical activation after the furnace is cooled to room temperature, and then crushed to 400 meshes, sealed and stored for standby use, and the mass fractions of the chemical components contained in the reinforcing agent are shown in Table 4 below:
[0080] Table 4
[0081]
[0082] The total mass proportion of the recycled aggregate from construction waste and the natural sand filler is 80% based on dry matter, and the mass ratio of the recycled aggregate from construction waste and the natural sand filler is 50:50, the mass proportion of the silicate cement binder is 20%, and the added mass of the reinforcing agent is 8% of the mass of the dry material, the added mass of the inducing agent water glass is 7% of the mass of the dry material, and the added mass of water is 12% of the mass of the dry material;
[0083] Step 2, compression molding: the preformed material obtained in step 1 is placed into a mold and then subjected to static compression molding to obtain a compact; the static compression molding pressure is 20 MPa, and the loading speed is not greater than 0.8 MPa / s;
[0084] Step 3, carbon dioxide curing: the green compact obtained in step 2 is placed in a steam curing kettle tank 3 in a carbon dioxide curing device and sealed, carbon dioxide is introduced into the steam curing kettle tank 3 through a carbon dioxide compensator 2, and the saturated carbon dioxide battery liquid in a carbon dioxide absorption tank 4 is simultaneously sent into a steam generator 5, and the green compact is subjected to carbon dioxide curing to obtain a permeable brick for a wall material;
[0085] The carbon dioxide battery liquid is a mixed liquid of water and an absorbent, wherein the absorbent is prepared by mixing lithium slag, sodium hydroxide, lithium carbonate, and potassium carbonate in a mass ratio of 1:1:1.5:1, calcining at 600° C. for 30 minutes, and then grinding to 300 meshes, and the solid-liquid ratio of the carbon dioxide battery liquid is 1:100;
[0086] The specific process of the carbon dioxide curing is as follows: the vacuum pump 1 is turned on to evacuate the curing kettle body 3 to a pressure of -0.06MPa, the vacuuming is stopped and the pipeline is closed to stabilize the pressure in the curing kettle body 3, and then the carbon dioxide compensator 2 is turned on to introduce carbon dioxide into the curing kettle body 3 until the pressure reaches 0MPa, and then the pressure is stopped for 5 minutes, and at the same time, the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank 4 is sent to the steam generator 5 through the feeding pipe, and the heating rod 6 is started for heating, and the pressed green body is subjected to carbon dioxide curing, the curing temperature is 180°C, the pressure in the kettle is 0.8MPa, and the pressure and temperature holding time is 3h, and then the used carbon dioxide battery liquid is sent to the carbon dioxide absorption tank 4 through the liquid outlet pipe, and the curing kettle body 3 is depressurized.
[0087] After testing, the product indicators such as strength, wear resistance, and permeability coefficient of the permeable bricks prepared in this embodiment all meet the requirements of GB / T25993-2023 "Permeable Pavement Bricks and Permeable Road Panels".
[0088] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing wall materials using a carbon dioxide curing process, characterized in that: The method uses aggregate, filler, cementitious material, reinforcing agent, inducing agent and water as raw materials, and prepares wall materials through primary stirring, secondary stirring, static standing, pressing and forming, and carbon dioxide curing.
2. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 1, characterized in that: The aggregates are derived from natural aggregates and recycled aggregates from construction waste, and the fillers are derived from natural sand, artificial sand, recycled sand from construction waste and industrial tailings sand. The particle size of the aggregates is 3mm to 5mm, and the particle size of the fillers is less than 1.5mm.
3. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 2, characterized in that: If the wall material is pavement bricks, the mass proportion of aggregates in the raw material aggregates and fillers is less than 30%, and the mass proportion of fillers is greater than 70%; or if the wall material is permeable bricks, the mass proportion of aggregates in the raw material aggregates and fillers is greater than 40%, and the mass proportion of fillers is less than 60%.
4. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 1, characterized in that: The cementitious material is silicate cement, the raw material of the reinforcing agent is two or more of dolomite, mica, lime and diopside, and the reinforcing agent contains the following chemical components by mass fraction: CaO>30%, MgO+Na2O+K2O>10%, SO3<0.50%, and the reinforcing agent is prepared by a low-temperature thermal activation process: the reinforcing agent raw material is placed in an electric furnace and kept at 80°C for 20 minutes, 110°C for 1 hour, 400°C for 20 minutes, and 600°C for 1 hour, and after the temperature is cooled to room temperature with the furnace, it is immediately transferred to a crusher for mechanical activation, and then crushed to 400 meshes, and sealed and stored for standby use; the inducing agent is water glass or sodium hydroxide.
5. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 1, characterized in that: The total mass of the aggregate and filler accounts for 80% to 90% of the dry material, the mass of the cementitious material accounts for 10% to 20%, the mass of the reinforcing agent added is 5% to 10% of the dry material mass, the mass of the inducing agent added is 3% to 5% of the dry material mass, and the mass of the water added is 10% to 20% of the dry material mass. The preparation process comprises the following steps: Step 1, mixing and standing the raw materials: weigh the aggregate, filler, cementitious material, and reinforcing agent, pour them into a mixer for dry material mixing to obtain a mixed dry material, and at the same time weigh the inducer and water, pour them into a high-speed mixer for wet material mixing to obtain a mixed slurry, and then introduce the mixed slurry into the mixed dry material for secondary mixing, and then stand to obtain a preformed material; Step 2: Compression molding: the preformed material obtained in step 1 is placed into a mold and then subjected to static compression molding to obtain a pressed blank; Step 3, carbon dioxide curing: the green compact obtained in step 2 is placed in a steam curing kettle body (3) in a carbon dioxide curing device and sealed, carbon dioxide is introduced into the steam curing kettle body (3) through a carbon dioxide compensator (2), and the saturated carbon dioxide battery liquid in a carbon dioxide absorption tank (4) is simultaneously sent into a steam generator (5), and the green compact is subjected to carbon dioxide curing to obtain a wall material.
6. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 5, characterized in that: In step 1, the speed of stirring the dry material is 20r / min, and the stirring time is 3min; the speed of stirring the wet material is 500r / min, and the stirring time is 2min; the speed of the secondary stirring is 45r / min, and the stirring time is 2min; the standing time is 1h to 4h.
7. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 5, characterized in that: The static pressure molding pressure in step 2 is not less than 25 MPa, and the loading speed is not greater than 0.8 MPa / s.
8. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 5, characterized in that: The carbon dioxide battery liquid in step three is a mixed liquid of water and an absorbent, wherein the absorbent is prepared by mixing lithium slag, sodium hydroxide, lithium carbonate, and potassium carbonate in a mass ratio of 1:1:1.5:1, calcining at 600°C for 30 minutes, and then grinding to 300 mesh, and the solid-liquid ratio of the carbon dioxide battery liquid is 1:
100.
9. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 5, characterized in that: In step 3, when the wall material is a pavement brick, the specific process of carbon dioxide curing is as follows: opening the vacuum pump (1) to evacuate the curing kettle body (3) to a pressure of -0.1 MPa, stopping the evacuation and closing the pipeline to stabilize the pressure in the curing kettle body (3), then opening the carbon dioxide compensator (2) to introduce carbon dioxide into the curing kettle body (3) until the pressure reaches 0 MPa, then stopping and stopping for 5 minutes, and at the same time, sending the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank (4) into the steam generator (5) through the feed pipe, starting the heating rod (6) for heating, and performing carbon dioxide curing on the pressed green body, the curing temperature is 180° C., the pressure in the kettle is 0.8 MPa, the pressure and temperature holding time is 5 hours, and then sending the used carbon dioxide battery liquid into the carbon dioxide absorption tank (4) through the liquid outlet pipe, and releasing the pressure of the curing kettle body (3).
10. A method for preparing wall materials using a carbon dioxide curing process as claimed in claim 5, characterized in that: In step 3, when the wall material is a permeable brick, the specific process of carbon dioxide curing is as follows: opening the vacuum pump (1) to evacuate the curing kettle body (3) to a pressure of -0.06MPa, stopping the evacuation and closing the pipeline to stabilize the pressure in the curing kettle body (3), then opening the carbon dioxide compensator (2) to introduce carbon dioxide into the curing kettle body (3) until the pressure reaches 0MPa, then stopping and stopping for 5 minutes, and at the same time, sending the saturated carbon dioxide battery liquid in the carbon dioxide absorption tank (4) into the steam generator (5) through the feed pipe, starting the heating rod (6) for heating, and performing carbon dioxide curing on the pressed green body, the curing temperature is 180°C, the pressure in the kettle is 0.8MPa, the pressure and temperature holding time is 3h, and then sending the used carbon dioxide battery liquid into the carbon dioxide absorption tank (4) through the liquid outlet pipe, and releasing the pressure of the curing kettle body (3).
Citation Information
Patent Citations
Recycling and reusing method of cement concrete waste
CN105985075A
Carbon dioxide cured prefabricated water-permeable concrete and preparation method thereof
CN109824321A
Preparation process of steel slag-based water permeable brick cured by hydration-carbonization coupling system and steel slag-based carbonized water permeable brick
CN114538849A
Method for preparing building material for roadbed and pavement from building solid waste based geopolymer
CN116751002A